Survey and Planning in Soil Conservation - Ghumare, N.K. (Journal of Soil and Water Conservation, 2022)
In any Soil Conservation planning the utilization of land resources obviously must form a major item, especially in India, where more than three fourths of the population depends primarily for their livelihood on land. A rapidly increasing population, a definitely insufficient level of nutrition of both man and livestock, and poverty partly caused by the low acreage per capita, warrant that utmost care should be taken of our land resources and they should be conserved against loss and deterioration and further at any cost be main-tained at a level of optimum productivity.